EFEKTIVITAS PERMAINAN BAHASA ARAB DALAM MENINGKATKAN KEMAMPUAN MEMBACA MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA ARAB - Sarah N Latuconsina (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2018)
This study aimed to analyse the students’ reading ability and to analyse the effectiveness of Arabic game in improving reading ability among the students of Arabic Language Education Department FBS UNM. It employed quasi-experimental method with pre-test and post-test non-equivalent control group design. The results of SPSS analysis showed that the use of Arabic game media was not effective in learning Arabic reading skills. This was evidenced by he sig value (2 tailed) of both class A and B post-test were 0.50, the sig value. = 0.05. So H0 was accepted and there was no significant difference between post-test of both experiment and control class. But this finding proves that the reading ability of the control class students was very good. Whereas in the experimental class, Arabic Reading ability was not good before treatment yet after treatment, the difference in the value of the pre-test and post-test was very significant.